Key for First Recorded Dragonfly (Odonata: Anisoptera) Fauna of District Lower Dir, Khyber Pakhtunkhwa, Pakistan - Perveen, Farzana; Khan, Anzela; Rauf, Sayed Abdul (International Research Journal of Insect Sciences, 2014)
Dragonflies (Odonata: Anisoptera) are beautiful insects with high species diversity worldwide. These insects are indicators of environmental pollution and are predators of important insect vectors of human pathogens and parasites, especially mosquitoes. The present research was the first record of 318 specimens of dragonflies from district Lower Dir (LD), Khyber Pakhtunkhwa, Pakistan collected during May-July 2011. Among the specimens collected there were 11 species, 7 genera and 3 families. The number of specimens collected in each family were 17 Cordulegasteridae (5.3%), 18 Gomphidae (5.7%), and 283 Libellulidae (89.0%). All cordulegastrids were the golden ringed, Cordulegaster brevistigmata brevistigmata Selys. All gomphids were Clubtails, Onychogomphus bistrigatus Selys. Libellulids species were: blue or black percher, Diplacodes lefebvrei (Rambur); ground skimmer, D. trivialis Rambur; black tailed skimmer, Orthetrum cancellatum (L); common red skimmer, O. pruinosum neglectum (Rambur); slender skimmer, O. sabina (Drury); triangle skimmer, O. triangulare triangulare (Selys); wandering glider or global skimmer, Pantala flavescens (Fabricius); spine legged redbolt, Rhodthemis rufa (Rambur) and common skimmer, Sympetrum decoloratum Selys. A dichotomous key based on external morphology, coloration and wing venation was prepared to facilitate the identification of the dragonfly fauna of the LD and aid conservation efforts of dragonflies in Pakistan.